Loss of skeletal muscle during systemic chemotherapy is prognostic of poor survival in patients with foregut cancer. Issue 2 (9th January 2018) - Daly, Louise E.; Ní Bhuachalla, Éadaoin B.; Power, Derek G.; Cushen, Samantha J.; James, Karl; Ryan, Aoife M.
Abstract: Background: Malnutrition, weight loss, and muscle wasting are common in patients with foregut cancers (oesophagus, stomach, pancreas, liver, and bile ducts) and are associated with adverse clinical outcomes. However, little is known about the changes in body composition that occur in these patients during chemotherapy and its impacts clinical outcomes. Patients and methods: A prospective study of adult foregut cancer patients undergoing chemotherapy between 2012 and 2016 was conducted. Computed tomography images were evaluated for cross‐sectional skeletal muscle area (SMA) and adipose tissue area (ATA) at two time points [interval 118 days (IQR 92–58 days)]. Longitudinal changes in SMA and ATA were examined using paired t ‐tests. Sarcopenia and low muscle attenuation (MA) were defined using published cut‐points. Cox proportional hazards models were used to estimate mortality hazard ratios for key predictors. Results: A total of 225 foregut cancer patients were included (67% male, median age 66 years). At baseline, 40% were sarcopenic, 49% had low MA, and 62% had cancer cachexia. Longitudinal analysis ( n = 163) revealed significant reductions in SMA [−6.1 cm 2 (3.9%)/100 days, P < 0.001]. Patients treated with neoadjuvant chemotherapy experienced greater losses in SMA and skeletal muscle mass compared with patients receiving palliative chemotherapy [−6.6 cm 2 (95%, confidence interval, CI: −10.2 to −3.1), P < 0.001 and −1.2 kg (95% CI: −1.8 to −0.5), P < 0.001, respectively]. Neither sarcopenia nor low MA at baseline was associated with reduced survival. A loss of SMA >6.0%/100 days (highest fourth) independently predicted overall survival in patients receiving palliative chemotherapy [hazard ratio: 2.66, (95% CI: 1.42 to 4.97), P = 0.002]. Conclusions: Patients with foregut cancers, particularly those treated with neoadjuvant chemotherapy, experience significant losses of muscle during chemotherapy. A high level of SMA loss is prognostic of reduced survival in patients treated with palliative chemotherapy. Multimodal interventions to stabilize or increase muscle mass and influence outcome warrant further investigation.